A comparison of anti‐arrhythmic efficacy of carvedilol vs metoprolol succinate in patients with implantable cardioverter‐defibrillators. Issue 2 (14th January 2019) - Ayan, Mohamed; Habash, Fuad; Alqam, Bilal; Gheith, Zaid; Cross, Michael; Vallurupalli, Srikanth; Paydak, Hakan
Abstract : BACKGROUND: The effects of carvedilol and metoprolol succinate on appropriate and inappropriate implantable cardioverter defibrillator (ICD) therapy in patients with heart failure with reduced ejection fraction (HFrEF) are not fully understood. HYPOTHESIS: The hypothesis of our study is possible carvedilol superiority over metoprolol in patients with ICD. METHODS: All patients with ICD registered to a single device clinic between 1/2012 and 6/2017 (n = 569) were identified. Patients with systolic heart failure (left ventricular ejection fraction ≤40%) treated with carvedilol vs metoprolol succinate were compared. Primary endpoint was difference in survival free of appropriate device therapy (shock or anti‐tachycardia pacing, ATP). Secondary endpoints were freedom from inappropriate therapy (shock or ATP) and all cause death. RESULTS: A total of 225 patients were included in the analysis with median follow up of 57 months (IQR 33.7‐90). The 2 groups were comparable in the baseline characteristics. Carvedilol was superior to metoprolol succinate in improving survival free of appropriate ICD therapy (HR 0.42; 95% CI 0.24‐0.72, P = 0.01). This difference was driven by reduction in survival free of appropriate shocks (HR 0.30; 95% CI 0.15‐0.63, P = −0.01) while there was no significant difference in appropriate ATP (HR 0.55; 95% CI 0.28‐1.1, P = 0.12). There was no significant difference in time to inappropriate shocks (HR 1.02; 95% CI 0.19‐5.6, P = 0.97), inappropriate ATP (HR 0.93, OR 0.24‐3.5, p value 0.9) or all cause death (HR 0.8; 95% CI 0.42‐1.5, P = 0.52). CONCLUSIONS: This study suggests that carvedilol use was associated with improved survival free of appropriate ICD therapy compared to metoprolol succinate in patients with HFrEF.